Desain Pembelajaran dalam Upaya Meningkatkan Kemampuan Pemecahan Masalah Siswa pada Topik Trigonometri - Laely Astafiani Azima (Griya Journal of Mathematics Education and Application, 2023)
This study aims to add alternative learning options to trigonometry material at the high school level by applying the problem based learning model. In developing the learning model, this research uses a learning design. Learning development is done by analyzing the needs and analyzing students. Performances objectives and learning outcomes are reviewed in detail and adjusted to the learning objectives that have been set. The results of this study indicate that the learning design by applying the problem based learning model can be one of the recommendations for teachers in implementing trigonometry learning. This is because in the learning process, students are asked to solve problems in the real life, so it can help students develop problem-solving skills in trigonometry.